The Caesar’s Wealth before the Watchdog: A Precision Journalism analysis about financial transparency of Government Cabinet in Spain - Tejedor Fuentes, Laura; Dader García, José Luis (Estudios sobre el Mensaje Periodístico, 2012)
The administrative information about top officials and civil servants’ activities in Spain is still kept under important restrictions. Such limitation is particularly severe on personal data of any type related to these politicians, in accordance with the Spanish preference for protection to privacy over the right to public interest information. Even so, since 2009 some regulations openness has taken place in relation to Government and Parliament members’ declarations about their assets, their personal economic interests and their business ties. The new regulation supposes a tiny advance towards a democratic transparency of general interest administrative documentation. Through the access to the specific data bases, precision journalism –a newsmedia strategy specialized on computer cross-checking and matching of big data collections-, contributes to a real democratic transparency by means of the disclosure of unveil irregularities, institutional unbalances or just basic data about public servants’ activities which can improve the control of the public institutions responsiveness by the citizens. Across an accurate data petition and the access to the specific datafiles recently unlocked to the public scrutiny in Spain, this article shows the results of an application of precision journalism to the case of the main directors of the executive power regarding their personal assets, complementary incomes and business connections. Nevertheless, the poor data specification showed in the disclosure records of the Spanish Administration seriously restricts the goal of a full watchdogging of the political representatives.
Keywords: public information; access to administrative information; democratic transparency; precision journalism; journalistic investigation; database matching.